A First-Principle study of the O, O2, OH, and HO2 adsorption on the Fe (100) surface - Muhamad Akrom (Unversitas Muhammadiyah Mataram, 2021)
Abstract: The purpose of this study was to investigate the interaction between O, O2, OH, and HO2 species on the Fe(100) surface using the DFT method. The DFT calculation provides specific information of the electronic structure of a molecules in ground state. The results show that the O atom preferred to be adsorbed on the hollow site, the OH species was adsorbed on the bridge site, while the O2 molecule was dissociated into two O atoms where both were adsorbed on the hollow site. Furthermore, when the H atom is attached to one of the O atoms of the dissociated O2 molecule, the OH species is formed which is adsorbed at the bridge site, and another O atom which remains adsorbed at the hollow site. This study can provide preliminary information on the adsorption mechanism of O, O2, OH, and HO2 species in explaining the electrochemical corrosion mechanism in our next work.Abstrak: Penelitian ini bertujuan untuk mengetahui interaksi antara spesi O, O2, OH, dan HO2 pada permukaan Fe(100) menggunakan metode DFT. Perhitungan DFT memberikan informasi spesifik tentang struktur elektronik molekul dalam keadaan dasar. Hasil penelitian menunjukkan bahwa atom O lebih suka teradsorpsi pada situs berongga, spesi OH teradsorpsi pada situs jembatan, sedangkan molekul O2 terdisosiasi menjadi dua atom O dimana keduanya teradsorpsi pada situs berongga. Selanjutnya, ketika atom H terikat pada salah satu atom O dari molekul O2 terdisosiasi, terbentuk spesies OH yang teradsorpsi di situs jembatan, dan atom O lain yang tetap teradsorpsi di situs berongga. Penelitian ini dapat memberikan informasi awal tentang mekanisme adsorpsi spesi O, O2, OH, dan HO2 dalam menjelaskan mekanisme korosi elektrokimia pada penelitian kami selanjutnya.